Mode of delivery, order of birth, parental age gap and autism spectrum disorder among Malaysian children: a case-control study - Galvan, Jo Ann Andoy; Ramalingam, Prabhagari Nair; Patil, Sapna Shridhar; Shobri, Muhammad Aminul Syahmi; Chinna, Karuthan; Sahrir, Muhammad Sabri; Chidambaram, Kumarappan (Elsevier Science Direct Ltd., 2020)
Rising prevalence of autism spectrum disorders (ASD) in the last decades has led research to focus on the diagnosis and identification of factors associated with ASD. This paper sought for possible factors that put children at risk for ASD. In this study, we investigated the association between ASD and parental ages, parental age gaps, birth order and birth delivery method in Malaysian population. In this school-based case control study, 465 children with ASD 464 controls participated. Questionnaires were distributed to the parents of the selected children through the respective principals. Among the tested variables, Caesarean section (OR = 1.63, 95% CI 1.20, 2.20), earlier order of birth in the family (OR = 0.68, 95% CI 0.59, 0.77) and increasing gap in parental ages (OR = 1.04, 95% CI 1.001, 1.07) were significantly associated with ASD. This study concludes that Caesarean section, earlier order of birth in the family and increasing gap in parental age are independent risk factors for developing autism among Malaysian children.